Cultural and educational synthesis a modern public library as a platform of social and spatial connectivity for the Luneta Park and Taft Avenue - Caluya, Flora Dianne R.
Manila's growth as a primary urban center and a melting pot of highly progressive economic, physical, and cultural aspects of society is a fact that people have accepted from the past until today. However, its development, although largely positive, has continually left behind some negative traces that accumulated until they became problems that can be discerned just by examining them through the naked eye. One such problem is the overall neglect of spaces that are of cultural and historical value due to rapid urbanization and uncoordinated modern developments ; which eventually led to the limited integration of Manila's urban fabric. Specifically Ermita as the central point of interaction between the districts of Manila as well as the focal point of integration between the city's 2 main industries -- Tourism and education, has affected physical and social spaces in such a way that resulted to the incoherence of the people with their environment, culture and their relationships. Through this thesis that focuses on integrating the various aspects of society with the built environment, synthesis of culture and education is emphasized as a vital platform to create spacial connectivity and social cohesion. Effectively, through the revitalization of the Manila City Library, the people, the spaces and its culture can come together to form a socially coherent landscape of experience and learning.